Chromosome-scale assembly of apple mint (Mentha suaveolens) - Alana Firl; Meric C. Lieberman; Nestor Kippes; Helen Tsai; Eric Dowd; Luca Comai; Isabelle M. Henry (BMC Genomic Data)
Abstract Objectives Mint oil is used in various commercial applications world-wide. Mint oil is typically harvested from commercial clones of peppermint or spearmints. Spearmints are the product of a cross between two diploid species: Mentha longifolia (horse mint) and Mentha suaveolens (apple mint). Peppermints are the product of an additional hybridization step between spearmint and an octoploid Mentha aquatica (water mint). Here, we present a chromosome-scale assembly of the genome of a clone of M. suaveolens. Together with the previously assembled genome of M. longifolia, these assemblies are instrumental in addressing questions regarding the origins of spearmint and peppermint oil and the genomic composition of commercial spearmints, and to start elaborating strategies for mint cultivar improvement. Data description A Falcon assembly of the genome of M. suaveolens was generated from 103X coverage of PacBio long reads. Additional scaffolding was conducted by Dovetail Genomics, using a Chicago library, and a HiC library. The resulting assembly had an N50 of 44.7 Mb, and 98.45% of the 536 Mb of the assembly were contained within 12 large superscaffolds. Finally, a genetic map was applied to correct persistent misjoins. Illumina RNA-Seq libraries from a variety of tissues were used to annotate the genome.